Rapid and Efficient N-tert-butoxy carbonylation of Amines Catalyzed by Sulfated Tin Oxide Under Solvent-free Condition - Kumar, J. K. Prashanth; Thirupathi, Boningari; Devaiah, Damma; Prasad, Avvari N.; Smirniotis, Panagiotis; Reddy, Benjaram M. (Orbital: The Electronic Journal of Chemistry, 2018)
A straightforward, rapid, and efficient protocol for the N-tert-butoxy carbonyl (N-Boc) protection of amines (aromatic, aliphatic) using sulfated tin oxide catalyst is illustrated. N-Boc protection of various amines was carried out with (Boc)2O using sulfated tin oxide as a catalyst at room temperature under solvent-free conditions. Rapid reaction times, ease of handling, cleaner reactions, easy work-up, reusable catalyst, and excellent isolated yields are the striking features of this methodology which can be considered to be one of the better methods for the protection of amines and alcohols. DOI: http://dx.doi.org/10.17807/orbital.v10i7.1155